Acquisition of T790M resistance mutation in a patient with advanced adenocarcinoma harboring uncommon EGFR mutations: a case report and literature review - Hakozaki T (OncoTargets and Therapy, 2019)
Taiki Hakozaki, Makiko Yomota Department of Thoracic Oncology and Respiratory Medicine, Tokyo Metropolitan Cancer and Infectious Diseases Center Komagome Hospital, Tokyo, Japan Background: Osimertinib is the standard of care for patients with non-small-cell lung cancer (NSCLC) patients harboring acquired EGFR T790M resistance mutation. However, the frequency of T790M resistance mutation acquisition and the efficacy of osimertinib in patients harboring uncommon EGFR mutations, which accounts for approximately 10% of EGFR mutations, remain unclear. Case presentation: We present the case of a 72-year-old Japanese woman with recurrent NSCLC harboring uncommon EGFR mutations, who was subsequently found to have acquired the T790M resistance mutation and was treated with osimertinib. She died 9 days later because of worsening respiratory failure with disease progression. Conclusion: The findings of the present case suggest that the T790M resistance mutation can occur even when the patient harbors an uncommon EGFR mutation after EGFR-tyrosine kinase inhibitor treatment, and the prognosis could be poor despite the presence of an acquired T790M resistance mutation. Keywords: non-small-cell lung cancer, EGFR-TKIs, osimertinib, uncommon EGFR mutation, acquired resistance